The hyperekplexias and their relationship to the normal startle reflex. - Brown, P; Rothwell, J; Thompson, P; Britton, T; Day, B; Marsden, C (1991)
The startle response to unexpected auditory and somaesthetic stimulation was studied in 8 patients with hereditary or symptomatic hyperekplexia. It was abnormal in its resistance to habituation and in its exaggerated motor response. Both noise and taps to the face and head elicited a normal early blink response, separate from the subsequent true startle reflex. The earliest reflex EMG activity recorded after the blink was in sternocleidomastoid. EMG activity in masseter, and trunk and limb muscles followed later. This pattern of muscle recruitment suggests a brainstem origin for the abnormal startle responses. In addition, the abnormal startle responses exhibited disproportionately long latencies to the intrinsic hand and foot muscles and relatively slow recruitment of caudal muscles. The pattern of muscle recruitment was similar between patients, irrespective of the absolute latency of the response, and regardless of whether stimulation was auditory or somaesthetic. This suggests that auditory and somaesthetic afferents converge on a common brainstem efferent system, and that this system forms the final common pathway for abnormal startle responses of differing latency. The characteristics of this efferent system differ from those previously described in brainstem reticular reflex myoclonus, but are similar to those described in the normal auditory startle reflex in man. This suggests that the abnormal startle response in hyperekplexia, and the normal startle reflex represent pathological and physiological activity in the same brainstem efferent system.